Indonesian Manuscripts at Staatsbibliothek zu Berlin: A Codicological Review (KEMANUSIAAN The Asian Journal of Humanities, 2023)
Old manuscripts are cultural products of the ancestors of modern Indonesians and contain highly valuable cultural information. As such, they were sought after by other nations, who have managed to acquire them in various ways, including by taking them, bartering them with other items or buying them. It is thus no wonder that a lot of Indonesian manuscripts are now housed in various institutions in other countries, including the Staatsbibliothek zu Berlin (STABI) in Germany. This article aims to describe the Indonesian manuscripts that are now housed in STABI and to trace how they ended up there, with a particular focus on the physical condition of the manuscripts using the codicological approach. As the research shows, the Indonesian manuscripts housed in STABI are from various regions, including Java, the Batak lands, Aceh, Bima, Lampung and Makassar, and in the Malay language used all over Southeast Asia. The manuscripts date from the 15th century onwards, and they were acquired as a result of purchase or as gifts from certain institutions or individuals.